2001
DOI: 10.1080/02626660109492837
|View full text |Cite
|
Sign up to set email alerts
|

Tropical cyclones and floods in Fiji

Abstract: Daily flow records, rainfall data and tropical cyclone maps during 1970-1998 are used to document the impact of tropical cyclones (TCs) on floods in the Rewa River system, Viti Levu, Fiji. Floods are large, brief, isolated events caused by TCs and non-TC tropical rainstorms. More floods are caused by tropical rainstorms than by TCs, but TC floods are larger. The log Pearson Type III distribution consistently provided the best fit to partial duration flood series and the widelyrecommended generalized Pareto dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 20 publications
(25 reference statements)
2
26
0
Order By: Relevance
“…5). Contrary to Kostaschuk et al (2001) and Terry et al (2001), who determined from a 30-year flow record that the peak discharge of TC-induced Rewa River floods was inversely related to the SOI, this study, using a much longer time series, could find no significant relationship between the peak heights of TC-induced Ba River floods and SOI (Fig. 5).…”
Section: El Niño-southern Oscillationmentioning
confidence: 39%
“…5). Contrary to Kostaschuk et al (2001) and Terry et al (2001), who determined from a 30-year flow record that the peak discharge of TC-induced Rewa River floods was inversely related to the SOI, this study, using a much longer time series, could find no significant relationship between the peak heights of TC-induced Ba River floods and SOI (Fig. 5).…”
Section: El Niño-southern Oscillationmentioning
confidence: 39%
“…The log Pearson type III statistic can be used to provide an "industry standard" of bankfull discharge for a river at a particular gaging station; times when discharge is greater than the bankfull discharge indicate the occurrence of a flood (IACWD, 1982). In the study of tropical cyclone floods in Fiji by Kostaschuk et al (2001), the log Pearson type III statistic was found to represent their partial duration flood series more accurately than the Pareto distribution, even though it tended to underestimate the largest flows slightly.…”
Section: Determining Bankfull Dischargementioning
confidence: 99%
“…However, there is some debate about changes in tropical cyclone frequency. Some research predicts that tropical cyclone frequency will increase (e.g., Greenough et al, 2001;Ouellet et al, 2012), while other research suggests that tropical cyclones are likely to intensify with global climate warming but occur less frequently (e.g., Irish and Resio, 2013;Kostaschuk et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations